REVITALISASI SISTEM PENYULUHAN PERTANIAN DALAM PERSPEKTIF MEMBANGUN INDUSTRIALISASI PERTANIAN PERDESAAN (Forum Penelitian Agro Ekonomi, 2013)
Extension is an integral part of agricultural development in rural areas. Rural farming system is the basis of economic activity for improving rural community life. On the other hand, the existing agricultural system does not support the competitive rural economy.  Rural agriculture industrialization considers agricultural system as an integrated unity of agricultural industry business with high-value added outputs. This paper describes the factors as prerequisites for agricultural extension system revitalization. There are three prerequisites for the revitalization, namely: (i) extension institution and organization, (ii) extension implementation, and (ii) extension workers. In the Extension System Revitalization program implemented by the government is not aimed to support agricultural industry in rural areas. This program is focused on improving extension internal institution and not specifically aimed to enhance extension material disseminated to the farmers. Transformation towards rural agricultural industry is not achieved through the improvement of internal extension institution only, but also through innovation topics specifically designed for extension. It is necessary to improve agricultural extension institution aiming at establishing rural agriculture industry.
Keywords: extension; agriculture; industrialization; rural; penyuluhan; pertanian; industrialisasi; perdesaan